Interpersonal Communication in Disclosing Gay Sexual Orientation to Friends - Sulistyana, Sulistyana (Telangke:Jurnal Telangke Ilmu Komunikasi, 2025)
The disclosure of gay sexual orientation to friends is a complex interpersonal communication process, particularly within the Indonesian cultural context, which is still influenced by social stigma and heteronormative norms. This study aims to understand the dynamics of interpersonal communication during the disclosure of gay sexual orientation, identify facilitating and inhibiting factors, and analyze friends' responses and their impact on friendships. Using an interpretive phenomenological qualitative approach, data were collected through in-depth interviews with five gay men aged 20-35 in Jakarta who had disclosed their sexual orientation to heterosexual friends. Thematic analysis revealed three main themes: (1) the disclosure process influenced by trust and relational context, (2) fear of rejection as the primary barrier, and (3) friends' responses ranging from acceptance to avoidance. The findings suggest that empathetic communication and a supportive social environment facilitate successful disclosure. This study contributes to interpersonal communication research by highlighting the importance of cultural sensitivity in disclosing sexual identity in Indonesia.